WILLIAM BLAKE’S VISIONARY POETRY AND ART: AN ANALYTICAL STUDY OF HIS CREATIVE GENIUS - Tagayeva Umida Ernazarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article examines the visionary poetry and art of William Blake, focusing on his unique combination of visual and literary expression to convey deep spiritual and social messages. By analyzing key elements of Blake’s thematic and symbolic approach, the study reveals how his works function as a response to the political, religious, and social transformations of his era. The study employs qualitative methods to analyze selected poems and artworks to understand Blake’s symbolic use of myth, religious archetypes, and prophetic visions.